Bibliometric Analysis of Publication in the Field of Artificial Intelligence and Cyber Security - Karakuş, Songül; Ay, Sevinç (MUSA YILMAZ, 2025)
With the rapid changes in technology, artificial intelligence and cybersecurity have become two important areas inseparable from each other in today's digital world. The aim of this article is to analyze academic research on artificial intelligence and cybersecurity using bibliometric analysis method by providing an overview of artificial intelligence and cybersecurity. The findings obtained from the bibliometric analysis conducted between 2002-2025 (available at the time of the search) using the Web of Science database revealed that there were a total of 1296 publications and 4023 authors related to artificial intelligence and cybersecurity. The most frequently used keywords were examined by the authors using the VOSviewer software, and as a result of this examination, cybersecurity was found to be repeated 344 times, and artificial intelligence was found to be repeated 238 times. It has been also seen that the data obtained included publications from 97 countries and the country with the highest number of publications has China with 282 publications. The relationships between artificial intelligence and cyber security technologies have been also visualized with VOSviewer software. While artificial intelligence has been suggested in the theme analysis, methods such as intrusion detection system and feature selection have been identified as niche themes. As a result, this study shows the current status of studies on artificial intelligence and cyber security. It is also thought to guide future studies in this field.
Keywords: Computer Software; Bilgisayar Yazılımı; Software Engineering (Other); Yazılım Mühendisliği (Diğer)